Sound and recording applications and theory - Rumsey, Francis (Routledge, 2021)
"Providing vital reading for audio students and trainee engineers, Sound and Recording is the essential guide for anyone who wants a solid grounding in both theory and industry practices in audio, sound, and recording. This updated and revised edition includes new content on automatic mixing, object- based audio formats, spatial mixing, and VR audio technology. This bestselling book introduces you to the principles of sound, perception, audio technology, and systems. Sound and Recording is the ideal audio engineering text for students, an accessible reference for professionals, and a comprehensive introduction for hobbyists"--
Includes index. - Description based on print version record and CIP data provided by publisher
Keywords: Sound -- Recording and reproducing; Son; Enregistrement et reproduction; MUSIC / Recording & Reproduction; Sound; Recording and reproducing